ANALISIS PENDAPATAN USAHATANI BAWANG DAUN DI DESA MANEMBO KECAMATAN PASSI TIMUR KABUPATEN BOLAANG MONGONDOW - Christofel Denis Ratu; Rine Kaunang; Tommy Fredy Lolowang (Sam Ratulangi University, 2020)
This study aims to analyze the income of leek farming in Manembo Village, Passi Timur Sub-district, Bolaang Mongondow Regency. This research lasted for 2 months, from November to December 2019. Sampling in this study was carried out by simple random sampling method with a number of respondents were 25 leek farmers. Primary data were collected through direct interviews using a list of questions (questionnaires) that have been prepared. Secondary data were obtained from the literature related to this research and related institutions. Data analysis used in this research is to use quantitative descriptive analysis and expenditure (production costs) to analyze the income of leek farming. The results showed that the income of onion farming in Manembo Village, East Passi District, Bolaang Mongondow District per farmer on average was IDR. 2,688,800.- *eprm*